Motorcycle accidents and their repercussions: an integrative review (Research, Society and Development, 2023)
Motorcycle accidents currently represent a significant portion of accidents caused by land transport, representing a highly complex problem that affects Brazil. In view of this, the present study of bus involvement was able to identify the main aspects of motorcycle accidents in the country. Using the integrative review as a study method, drawn from studies published in the literature between the period 2015-2022. The victims were mostly male, black/brown, between 20 and 29 years old and with low schooling. The incidents were caused in certain cases due to the use of alcoholic beverages, mainly on weekends, being aggravated due to the absence of helmets. It was also identified that in most events there was a need for hospitalization, in view of the sequelae generated, such as the presence of fractures. And despite the triggering aggravating factors, few actions are evolved in order to change this scenario. Finally, it should be noted that there is a need to implement practical and efficient actions, in order to bring about significant changes with regard to traffic accidents, in particular motorcycle accidents, which are now becoming one of the main social problems in Brazil.